PERSEPSI SISWA TERHADAP PENGGUNAAN MODUL PRAKTIKUM BIO BATERAI DALAM PEMBELAJARAN FISIKA SMA MATERI ENERGI TERBARUKAN - Pawarangan, Ishak; Tumewu, Widya Anjelia; Mawuntu, Vicky Julius; Kumendong, Igreya Mitchell (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2024)
This study aims to examine students' perceptions of the use of a bio-battery practicum module utilizing coffee grounds in physics education on the topic of renewable energy. The research involved 12 students from SMA Negeri 2 Tomohon as participants. The evaluation instrument consisted of a questionnaire with 11 questions grouped into three primary indicators: module appearance, material presentation, and module benefits. The findings revealed that the module appearance indicator was rated as excellent on three questions (100%, 83.33%, and 100%) and good on one question (66.67%). The material presentation indicator received excellent ratings across all questions, ranging from 83.33% to 100%. Similarly, the module benefits indicator achieved excellent ratings for all questions (100%). Despite these positive results, a few neutral responses were observed on questions concerning the module’s design and illustrations (33.33% and 16.67%) and material clarity (16.67%). Overall, the module demonstrated a high level of effectiveness, with the majority of scores exceeding 76%, placing it in the